2015
DOI: 10.1080/09205063.2015.1082807
|View full text |Cite
|
Sign up to set email alerts
|

A novel method of fabricating carbon nanotubes-polydimethylsiloxane composite electrodes for electrocardiography

Abstract: Polymer-based flexible electrodes are receiving much attention in medical applications due to their good wearing comfort. The current fabrication methods of such electrodes are not widely applied. In this study, polydimethylsiloxane (PDMS) and conductive additives of carbon nanotubes (CNTs) were employed to fabricate composite electrodes for electrocardiography (ECG). A three-step dispersion process consisting of ultrasonication, stirring, and in situ polymerization was developed to yield homogenous CNTs-PDMS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…As described in detail in the next paragraph, the preparation process of the MWCNT/PDMS involves multiple dispersion steps utilising ultrasonication, an organic solvent and mechanical stirring as in [ 38 , 39 , 40 , 41 , 42 , 43 ], to achieve a uniform distribution of the MWCNT filler particles within the elastomeric matrix and facilitate an isotropic composite conductivity. Due to the strong inter-tube Van der Waals attractive forces, CNTs form together highly aggregated agglomerates in their natural state and hence external mechanical energy is required to separate these aggregates [ 44 , 45 , 46 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…As described in detail in the next paragraph, the preparation process of the MWCNT/PDMS involves multiple dispersion steps utilising ultrasonication, an organic solvent and mechanical stirring as in [ 38 , 39 , 40 , 41 , 42 , 43 ], to achieve a uniform distribution of the MWCNT filler particles within the elastomeric matrix and facilitate an isotropic composite conductivity. Due to the strong inter-tube Van der Waals attractive forces, CNTs form together highly aggregated agglomerates in their natural state and hence external mechanical energy is required to separate these aggregates [ 44 , 45 , 46 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, there have been researches on finding the optimum solvents to disperse CNTs into specific polymer matrices such as PDMS . Interestingly, Liu and Choi reported that although some of the organic solvents worked well for the dissolution of PDMS and the dispersion of MWCNTs, separately, they might not work when they were used for dispersing the MWCNTs into the PDMS solution .…”
Section: Introductionmentioning
confidence: 99%
“…CNTs, carbon fibers (CFs), and their composites with different forms are the most commonly used materials in stretchable EP electrodes [48,49]. Liu et al mixed CNT as the conductive filler with PDMS to obtain a uniform CNTS-PDMS mixture; the signal amplitude measured by the ECG electrode manufactured using this mixture was equivalent to that of the Ag/AgCl electrode [50].…”
Section: Flexible Ep Electrodes Based On Conductive Polymersmentioning
confidence: 99%